Campur Kode dalam Tuturan Penjual dan Pembeli di Pasar Kaget Jalan Karya Satu Kabupaten Kampar - Febe Mariana; Ermawati Sulaiman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
This research is about code mixing in the utterances of sellers and buyers in the Pasar shocked Jalan Karya one, Kampar district. The problems discussed in this study are (1) What are the forms of code-mixing contained in the Speeches of Sellers and Buyers at Pasar Kaget Jalan Karya Satu, Kampar Regency? (2) What are the causes of code mixing between Sellers and Buyers at the Shocked Market Jalan Karya Satu, Kampar Regency?. The purpose of this study was to examine the form of code-mixing and the causes of code-mixing in the speech of sellers and buyers in the Pasar shocked Jalan Karya one, Kampar district. The theory that researchers use in this study is the theory of Abdul Chaer (2015). The method that the researcher uses is a descriptive method. The research results obtained are 1) The form of code mixing contained in the speech in the Pasar shocked Jalan Karya one Kampar district amounted to 5 forms, namely: insertion of elements in the form of words, phrases, baster, repetition of words, and expressions or idioms. (2) The factors that cause code-mixing in the speeches of sellers and buyers at the Pasar Pasar Minggu, Kampar Regency are (a) relaxed or informal situations, (b) the absence of appropriate expressions, (c) showing off their learning.